Examining the Relationship Between Financial Literacy, Attitude and Behavior Levels and Psychological Distress Levels of Healthcare Professionals - Melemezoğlu, Yağmur; Yaman, Kemal (International Review of Management and Marketing, 2025)
The main purpose of this study is to investigate whether there is a relationship between the financial literacy attitudes and behaviors of healthcare professionals and their psychological distress levels. The universe of the study consists of healthcare professionals working in a public hospital in Mersin City Center. The study was evaluated with data obtained from 281 healthcare professionals using a survey method. The data in the study were obtained using the “Personal Information Form”, “Financial Literacy Attitude and Behavior Scale” and “Psychological Distress Scale”. In the study, Student t test, One-Way ANOVA test and Correlation analysis were applied statistically. The study results revealed that there is a positive and moderately significant relationship between the financial literacy attitude and behavior levels of healthcare professionals and their psychological distress levels. In addition, it is concluded that there is relationship between the financial literacy attitude and behavior scale and the variables of gender, education level, age and income status; and between the psychological distress scale and the variables of occupation and income status.